Hemodynamic responses to emotional auditory stimuli in patients with prolonged disorders of consciousness: an fNIRS study - Zhang, Yuxuan; Duan, Bixuan; Cui, Hongxing; Zhu, Chuanhua; Huang, Binbin; Li, Hongwei; Li, Wei (Frontiers in Neurology, 2025)
BackgroundIn this study, we used functional near-infrared spectroscopy (fNIRS) to detect changes in cerebral blood flow in response to emotional auditory stimuli in patients with prolonged disorders of consciousness (pDoC). We aimed to verify whether hemodynamic responses to emotional auditory stimuli in pDoC patients measured via fNIRS differed significantly depending on the level of consciousness.MethodsfNIRS was used to assess brain function in 60 subjects, including 20 patients with unresponsive wakefulness syndrome (UWS), 19 patients in a minimally conscious state (MCS), and 21 healthy controls (HC). All the participants were exposed to emotional auditory stimuli, including the subject’s own name (SON), fear stimulus and infant crying stimulus. We identified the mean and slope value as biomarkers reflecting changes in brain function.ResultsFor the SON stimulus, mean HbO concentration analysis showed that the UWS group had significantly lower mean HbO concentration changes in the bilateral middle temporal gyrus (MTG), retrosubicular area (RSA), premotor and supplementary motor area (SMA), and specific channels of the right temporopolar area (TPA) and pars triangularis Broca’s area (PTG) compared to the HC group. The MCS group exhibited a significantly lower mean HbO concentration change in the right MTG compared to the HC group and a significantly greater change in the left SMA compared to the UWS group. No significant differences were found in the slope analysis across the three groups. For the fear stimulus, mean oxyhemoglobin (HbO) concentration analysis showed that the MCS group had significantly greater mean HbO concentration changes in the left TPA and dorsolateral prefrontal cortex (DLPFC) compared to the HC group. In the slope analysis, both the UWS and MCS groups exhibited significantly greater values in the left DLPFC compared to the HC group. For the infant crying stimulus, the slope analysis showed that the MCS group had significantly greater values in the frontopolar area (FPA) and left TPA compared to the HC group. However, no significant differences were observed in the mean HbO concentration analysis among the three groups.ConclusionThis study demonstrated that auditory stimuli, especially self-referential and emotionally salient sounds, elicit distinct cortical responses in patients with different levels of consciousness.